2021
DOI: 10.26623/julr.v4i1.3230
|View full text |Cite
|
Sign up to set email alerts
|

Kebijakan Hukum Pidana Dalam Upaya Penanggulangan Tindak Pidana Untuk Mengurangi Overcrowded Lembaga Pemasyarakatan Pada Masa Pandemi Covid-19

Abstract: <p>Peningkatan jumlah penghuni lembaga pemasyarakatan dapat memicu adanya permasalahan overcrowded. Overcrowded di lembaga pemasyarakatan juga rentan terhadap penularan Covid-19 yang saat ini masif terjadi.<strong> </strong>Dikeluarkannya kebijakan pemerintah berupa Kebijakan oleh Menteri Hukum dan Ham berupa Keputusan Menteri Hukum dan Ham No M.HH-19.PK.01.04.04 Tahun 2020, dan juga Permenkumham No 10 Tahun 2020 merupakan suatu hal yang tepat dan memperoleh dampak yang positif bagi keberlang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This can be observed in the substandard conditions and facilities provided to detainees or inmates in several prisons. The majority of prisons in Indonesia also suffer from overcrowding issues, with conditions falling below capacity standards (Ardiansyah, 2020;Fadhil, 2021;Fadilah & Subroto, 2023;Hamja, 2022;Isnawati, 2022;Jamilah & Disemadi, 2020;Lidya Suryani Widayati, 2012;Patras, 2020;Ricky Fahriza, 2020;Rizaldi, 2020;Saputra et al, 2021;Solehudin & Wibowo, 2021;Tobing, 2019;Wibowo & Subroto, 2022). Inadequate attention to nutritional aspects in meals, roofs made of materials that do not withstand heat, limited clean water facilities, and minimal amenities create challenges for inmates, especially vulnerable groups like women who have various biological vulnerabilities.…”
Section: Resultsmentioning
confidence: 99%
“…This can be observed in the substandard conditions and facilities provided to detainees or inmates in several prisons. The majority of prisons in Indonesia also suffer from overcrowding issues, with conditions falling below capacity standards (Ardiansyah, 2020;Fadhil, 2021;Fadilah & Subroto, 2023;Hamja, 2022;Isnawati, 2022;Jamilah & Disemadi, 2020;Lidya Suryani Widayati, 2012;Patras, 2020;Ricky Fahriza, 2020;Rizaldi, 2020;Saputra et al, 2021;Solehudin & Wibowo, 2021;Tobing, 2019;Wibowo & Subroto, 2022). Inadequate attention to nutritional aspects in meals, roofs made of materials that do not withstand heat, limited clean water facilities, and minimal amenities create challenges for inmates, especially vulnerable groups like women who have various biological vulnerabilities.…”
Section: Resultsmentioning
confidence: 99%
“…This means that there is overcapacity, even reaching 300% in several places in Indonesia. (Saputra, 2021) The condition of correctional institutions in Indonesia is overcrowded, where the ratio of inmates to correctional institutions and the capacity of correctional institutions are not proportional. The density of convicts in correctional institutions occurs due to several factors.…”
Section: Provisions For the Implementation Of The Implementation Of S...mentioning
confidence: 99%
“…The research that has been done previously, among others: first, research conducted by Violette S. R. Mokodongan (2021) found that the implementation of Large-Scale Social Restrictions (PSBB) regulated in Government Regulation Number 21 of 2020, as a derivative of Law Number 6 of 2018 concerning Health Quarantine, shows that the existence of the law is indispensable as a guide when the country is faced with an Extraordinary Event (KLB) that is troubling the world. [7] second, research conducted by Andika Oktavian Saputra (2021) shows that the policy of reducing the criminal period due to the COVID-19 pandemic to provide assimilation and integration to prisoners after fulfilling certain conditions is a progressive policy. [8] Based on the above explanations, this research will discuss issues related to "Criminal Policy in Realizing the Recovery of Socio-Political Conditions for National Resilience After the COVID-19 Pandemic".…”
Section: Introductionmentioning
confidence: 99%
“…[7] second, research conducted by Andika Oktavian Saputra (2021) shows that the policy of reducing the criminal period due to the COVID-19 pandemic to provide assimilation and integration to prisoners after fulfilling certain conditions is a progressive policy. [8] Based on the above explanations, this research will discuss issues related to "Criminal Policy in Realizing the Recovery of Socio-Political Conditions for National Resilience After the COVID-19 Pandemic". The problems that will be discussed in this study are:…”
Section: Introductionmentioning
confidence: 99%